PERBANDINGAN MODEL PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA POKOK BAHASAN HIDROKARBON - Aprilia Heny Sulistyawati; Apriani S. Parubak; Achmad Rante Suparman (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. This research aimed to knowing the difference of Think Pair Share (TPS) and Talking Stick learning model to learning outcomes, knowing the difference of learning style (visual, auditorial, and kinesthetic) to the learning outcomes, knowing the interaction between the learning model and the learning style. This research was used a quasi experimental research with 2 x 3 factorial design. Sampling technique was purposive sampling. Data collection techniques were used tests and questionnaires. The results showed that there was no difference of Think Pair Share (TPS) learning model and Talking Stick learning on learning outcomes, there were no learning style differences (visual, auditorial, and kinesthetic) to learning outcomes, and there were no the interaction between the learning model and the learning style.Keywords: The Think Pair Share (TPS) learning model, The Talking Stick learning model, learning style, learning outcomes